Improvement in the planarization of 4H-SiC(0001) achieved by photo-assisted chemical mechanical polishing (P-CMP) using nano TiO2-based composite abrasive with heterostructure - Shidong Chen; Hong Lei (Friction, 2025)
The planarization of silicon carbide (SiC), which is crucial for manufacturing power devices resilient to harsh working environments, has garnered significant attention. The utilization of titanium dioxide (TiO2)-based heterogeneous photocatalysts offers a promising avenue for achieving efficient polishing of SiC surfaces through photo-assisted chemical mechanical polishing (P-CMP) in an environmentally friendly manner. In this study, we employed nanodiamonds (NDs) and graphene oxide (GO) to fabricate a composite of TiO2/ND/GO abrasives. Subsequently, the P-CMP performance of TiO2/NDs/GO on the Si face of SiC was systematically investigated. High-resolution transmission electron microscopy (TEM) revealed the heterostructure between TiO2 and the NDs. Furthermore, the P-CMP results indicate that the heterostructure significantly enhances the polishing rate of the composite abrasives on SiC, achieving the highest material removal rate (MRR) of 600 nm/h and reducing the average surface roughness (Sa) to 1.1705 nm. Additionally, owing to the lubricating and dispersing effects of GO, the occurrence of ND aggregation is avoided, preventing scratching on SiC. The measurement of the ·OH concentration indicates that an increase in the ·OH concentration is the primary factor contributing to the improvement in the MRR. The results from wetting angle and friction coefficient tests revealed that the polishing slurry containing TiO2/NDs/GO exhibited excellent wettability and provided sufficient frictional force on the SiC surface. X-ray photoelectron spectroscopy (XPS) characterization demonstrated that TiO2/NDs/GO enhanced the degree of oxidation of the SiC surface, leading to the formation of a softer oxide layer. Finally, on the basis of the experimental and characterization results, a comprehensive analysis of TiO2/NDs/GO and P-CMP was conducted.